Subscriber's evaluation of the Computerized Index to Philippine Periodical Articles (CIPPA) - Azarcon, Adrian C. (2011)
This study was done to determine subscribers' satisfaction with the CIPPA. Additionally, it aims to determine the profile of the ideal periodical index according to the subscribers, determine how the CIPPA measures up to this ideal periodical index, and then based on the comparison come up with a recommendation for improving the CIPPA.